Broadband internet: An information superhighway to sex crime? - Manudeep Bhuller; Tarjei Havnes; Edwin Leuven; Magne Mogstad (Institute for the Study of Labor (IZA), 2011)
Does internet use trigger sex crime? We use unique Norwegian data on crime and internet adoption to shed light on this question. A public program with limited funding rolled out broadband access points in 2000-2008, and provides plausibly exogenous variation in internet use. Our instrumental variables and fixed effect estimates show that internet use is associated with a substantial increase in reported incidences of rape and other sex crimes. We present a theoretical framework that highlights three mechanisms for how internet use may affect reported sex crime, namely a reporting effect, a matching effect on potential offenders and victims, and a direct effect on crime propensity. Our results indicate that the direct effect is non-negligible and positive, plausibly as a result of increased consumption of pornography.
urn:nbn:de:101:1-201105173117
Keywords: J13; H40; I28; D31; 330; internet; broadband; instrumental variables; sex crimes; rape; pornography; Gewalt; Sexuelle Belästigung; Kriminalität; Internet; Medienverhalten; Breitbandkommunikation; Schätzung; Norwegen